Efficient Round-Optimal Secure Two-Party Computation from Sigma-protocol - Yonglong Tang; Chunming Tang (2010 International Conference on Communications and Mobile Computing, 2010)
In this paper, based on Σ-protocol on HC (a NP-complete language), we firstly construct a Σ-protocol for any NP language thm1 ∧ thm2, then transfer it into a non-interactive protocol from a hash function and a pseudo-random generator. Finally, we construct an efficient round-optimal secure two-party computation protocol from our non-interactive protocols.